2006
DOI: 10.1177/147323000603400312
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphometry of the Lower Lumbar Vertebrae: Osteometry in Dry Bones and Computed Tomography Images of Patients with and without Low Back Pain

Abstract: Various factors affect the development of the vertebral canal. The dimensions of the vertebral canal and the intervertebral foramen can be altered by these factors before or after birth. Sex differences in dimensions have also been reported. When there is a stenosis of the vertebral canal or the intervertebral foramen, neural structures confined within them can be affected easily, resulting in symptoms. Using computed tomography images, we compared vertebral canal dimensions in 100 patients with low back pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“… 14 Spinal canal depth in this study was observed to be narrowest at L3 (17.5 ± 0.53 mm) and greatest at L5 (19.7 ± 0.49 mm). 22 The overall mean midsagittal spinal canal diameter values measured in our study closely agree with the values reported by Panjabi et al Varol et al 23 reported mean spinal canal depths to range from 13.33 to 16.31 mm (SDs ranging from ± 1.88 mm to ± 2.52 mm) depending on spinal level and sex on CT images of 100 patients having low-back pain. On CT images in a control group of 40 individuals with no history of low-back pain, Varol et al reported mean spinal canal depths to range from 17.15 to 18.68 mm (SDs ranging from ± 1.82 mm to ± 2.23 mm) depending on spinal level and sex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 14 Spinal canal depth in this study was observed to be narrowest at L3 (17.5 ± 0.53 mm) and greatest at L5 (19.7 ± 0.49 mm). 22 The overall mean midsagittal spinal canal diameter values measured in our study closely agree with the values reported by Panjabi et al Varol et al 23 reported mean spinal canal depths to range from 13.33 to 16.31 mm (SDs ranging from ± 1.88 mm to ± 2.52 mm) depending on spinal level and sex on CT images of 100 patients having low-back pain. On CT images in a control group of 40 individuals with no history of low-back pain, Varol et al reported mean spinal canal depths to range from 17.15 to 18.68 mm (SDs ranging from ± 1.82 mm to ± 2.23 mm) depending on spinal level and sex.…”
Section: Discussionsupporting
confidence: 90%
“…On CT images in a control group of 40 individuals with no history of low-back pain, Varol et al reported mean spinal canal depths to range from 17.15 to 18.68 mm (SDs ranging from ± 1.82 mm to ± 2.23 mm) depending on spinal level and sex. 23 In a study investigating intervertebral foramen dimensions, Cinotti et al 18 found the mean minimal foraminal width to be 4.5 mm, with a range of 2.5 to 5 mm. The anterior-posterior spinal canal diameter (spinal canal depth) and the foraminal width measured in our study are within the range of results reported by Eisenstein, Postacchini et al, Ullrich et al, Panjabi et al, Varol et al, and Cinotti et al The slightly greater mean measurements we observed may be explained by the far smaller sample size and the location of the measurements in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicate success in regards to providing a 3D reconstruction of human vertebrae with 95% of vertices' errors less than 3.5 millimetres with a median of 1.1 millimetres. Single human vertebrae are commonly available around the world (Le Bras, et al, 2003;Varol, et al, 2006) however they have been mostly used for physical measurements (e.g. population parameters) and not for 3D reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Making such databases publicly available helps to advance the state-of-the-art in various medical and anatomical fields. The process of using callipers to measure real bone shape has been widely used especially in quantitative morphometric studies (Gour, Shrivastava and Thakare, 2011;Hurxthal, 1968;Kanani, et al, 2012;Varol, et al, 2006;Zamora, Sari-Sarraf and Long, 2003) and is considered the standard method for vertebrae measurements. However, using callipers is insufficient for constructing 3D models of bone shape, and such models are desirable for automatic and semi-automatic interpretation of medical images.…”
Section: Discussionmentioning
confidence: 99%
“…The transverse processes act as levers for the attachments of muscles and also articulate with the ribs in the thoracic region. The sagittal diameter of the vertebral foramen differs from about 15.3 mm to 16.5 mm in L3-S1, the diameter is larger in the male than the female (Varol et al, 2006). In humans, the transverse processes are short and laterally directed in the cervical region.…”
Section: The Vertebral Arch and Articular Processesmentioning
confidence: 99%